2020
DOI: 10.1123/apaq.2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Early Movement Matters: Interplay of Physical Activity and Motor Skill Development in Infants With Down Syndrome

Abstract: This longitudinal study investigated monthly motor development and physical activity (PA) of infants with and without Down syndrome. Gross and fine motor skills (Bayley Scales of Infant Development-III) and PA (accelerometer) were assessed in 35 infants at eight time points during infancy. A multivariate mixed model identified time points when motor scores diverged between the groups. In infants with Down syndrome, bivariate correlations between monthly PA and motor changes were calculated, and multivariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Thus, it can be inferred that there are delays in all aspects of the development of the body schema of DS children that are due to perceptual and motor deficits, which are responsible for the formation of the same and functional activities, and there must be an adequate stimulation that properly addresses the lags presented in each individual [ 58 ]. Differences in the development of gross and fine motor skills appear in DS children in the first months of life, with more active children achieving more marked development, highlighting the adaptability of early childhood and the importance of early stimulation [ 68 ], which also contributes to the development of functional skills, where people with DS underperform others [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be inferred that there are delays in all aspects of the development of the body schema of DS children that are due to perceptual and motor deficits, which are responsible for the formation of the same and functional activities, and there must be an adequate stimulation that properly addresses the lags presented in each individual [ 58 ]. Differences in the development of gross and fine motor skills appear in DS children in the first months of life, with more active children achieving more marked development, highlighting the adaptability of early childhood and the importance of early stimulation [ 68 ], which also contributes to the development of functional skills, where people with DS underperform others [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there was limited evidence regarding interventions on motor skills in individuals with DS (n = 15). This may be a concern as studies reported that individuals with DS experience motor skill deficits from early childhood, which may continue even as they age (Capio et al, 2018;Hauck et al, 2020;Zakaria et al, 2020). Regardless of the small number of included studies, the current meta-analysis found significant positive effects of interventions on motor skills in individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…Aligned with this phenomenon, evidence indicates that individuals with DS experience motor skill deficits (Capio et al, 2018;Hauck et al, 2020;Zakaria et al, 2020;Ku, 2020). A study found constant lower levels of both gross and fine motor skills in infants with DS compared to typically developing infants from the ages of 2 months (gross motor skills) and 4 months (fine motor skills) to 18 months (Hauck et al, 2020). Another study found that among 33 children with DS, 61.8% were categorized as below average in a motor skill assessment (Zakaria et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the research on adapted physical education (APE), efforts to participate in regular physical activity and to develop motor skills for children in APE programs were proven to have positive impacts in many studies (Esentürk and Yarımkaya, 2021; Hauck et al, 2020; Lai et al, 2020; Regaieg et al, 2021; Todd et al, 2021) [ 27 , 28 , 29 , 30 , 31 ]. Those studies were implemented based on treatments in health settings, organizational research, and various professional fields and supported by scientific and objective evidence, which is referred to as evidence-based practice (EBP; American Psychological Association, 2005; Williams and Glisson, 2014) [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%